Effect of components mal-alignment on biomechanics in fixed unicompartmental knee arthroplasty using multi-body dynamics model during a walking cycle. (February 2022) - Hu, Jiayu; Xiong, Ran; Chen, Xiaofei; Chen, Zhenxian; Jin, Zhongmin
Highlight: Musculoskeletal multibody models of unicompartmental knee arthroplasty were developed. Biomechanical property in the knee was quantified following coronal mal-rotation. Coronal mal-alignment could result in the aberrant biomechanical alterations of tibiofemoral joint. Coronal mal-alignment shows no influence on the biomechanics of patellofemoral joint. Component overcorrections in coronal plane should be avoided, especially mal-alignment exceeding 9°. Abstract: Aberrant knee biomechanical environment caused by the component mal-alignment of unicompartmental knee arthroplasty (UKA) could lead to knee pain and even early prosthetic failure. This study aims at quantifying the effects of the coronal mal-alignment of femoral and tibial components on biomechanics of knee joint during walking. A subject-specific musculoskeletal multibody model of UKA was established based on a model validated in our previous study. In this model, both of femoral and tibial components were re-aligned with the coronal angle ranging from 9° of varus to 9° of valgus at 3° increment, respectively. It was shown that the valgus mal-alignment of femoral component and the varus mal-alignment of tibial component caused a clearly increased trend in the contact force and valgus rotation of tibiofemoral joint, and in the medial collateral ligament and anterior cruciate ligament force, with the most remarkable alterations in the 9° condition. However, component mal-alignment had no effect on the biomechanical environment of patellofemoral joint. It is then advisable that surgeons should be concerned with coronal component position on UKA because of adverse biomechanical effects. Specifically, more than 9° of mal-alignment could lead to more detrimental effects.